An analysis of the responsibility to protect in relation to sovereignty and power - Kar, Cem Oğuz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
This study aims to analyze the United Nations’ (UN’s) concept of Responsibility to Protect by relating it to sovereignty and power in international relations. The concept discusses the limits of sovereignty in cases of atrocities. However, the concept’s practice has conditions for the five permanent members of the Security Council that include not using their veto power. The roles and involvements of these five states in the concept, and the issues surrounding the concept are decisive. They illustrate the state’s influence on international structure and principles. In this case, the sovereignty is related to responsibility as concept describes while decisions surrounding a situation are made by sovereign states. Thus, the concept faces differences in principle and in practice. The mission of preventing atrocities and understanding sovereignty as a responsibility in this perspective is shaping actions. The five permanent members of the Security Council determine military interventions by using the argument of the concept unilaterally, it will be detailed in the last chapter. However, these actions also include the interests of the five states, and while using the reasoning of the concept, these actions have also caused atrocities. In these cases, changes in the balance of international power are decisive in the practice of the concept. The Responsibility to Protect concept includes remarkable missions for humanity, however, practicing of the concept relies on sovereign state actions and it includes power dynamics.
Keywords: Responsibility to protect (International law)